APPLICATION OF SILVER COATING ON POLYMER MATERIALS IN NITRATE MELTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
. The release of metallic silver on the surface of polymers upon interaction with meltsof silver and ammonium nitrate has been studied.
Keywords: polymers, silver nitrate, ammonium nitrate.